Manajemen Pembelajaran dalam Meningkatkan Mutu Pendidikan di Madrasah - Mukarromah, Siti; Rosyidah, Arini; Musthofiyah, Dewi Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Learning management is the process of managing planning, organizing, controlling (directing), and evaluating activities related to the learning process of students by involving various factors in it, in order to achieve educational goals and seek to improve the quality of education. This study aims to determine the application of learning management to improve the quality of education in madrasas. This study uses a qualitative research method with a literature review approach. The results obtained illustrate the need for a learning management in improving abilities and skills to support the implementation of a quality education process according to the vision, mission and goals. Therefore, efforts to improve the quality of education are to organize education management, so an organization is needed to achieve common goals in more effective and efficient learning management to improve quality assurance so as to reduce obstacles in order to achieve the goals of quality madrasa instituti